2019
DOI: 10.1098/rsos.181482
|View full text |Cite
|
Sign up to set email alerts
|

Speed-mediated properties of schooling

Abstract: Collectively moving animals often display a high degree of synchronization and cohesive group-level formations, such as elongated schools of fish. These global patterns emerge as the result of localized rules of interactions. However, the exact relationship between speed, polarization, neighbour positioning and group structure has produced conflicting results and is largely limited to modelling approaches. This hinders our ability to understand how information spreads between individuals, which may determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
5
29
0
Order By: Relevance
“…[28,29]). Individual speed also strongly drove the alignment and temporal coordination of the pairs, in line with previous empirical studies that found fast moving groups tend to be polarised and slow moving groups to be disordered [12,13,30]. As in our study the robotic partner completely lacked any alignment rules, our findings provide novel empirical evidence that individual speed is a key factor facilitating group alignment and coordination.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…[28,29]). Individual speed also strongly drove the alignment and temporal coordination of the pairs, in line with previous empirical studies that found fast moving groups tend to be polarised and slow moving groups to be disordered [12,13,30]. As in our study the robotic partner completely lacked any alignment rules, our findings provide novel empirical evidence that individual speed is a key factor facilitating group alignment and coordination.…”
Section: Discussionsupporting
confidence: 90%
“…Although speed-mediated changes in local interaction rules may help to explain these effects [6,10], groups may be more likely to become disordered at lower speeds because of larger potential angular fluctuations at lower speeds, as is predicted from theoretical analysis [8]. Our finding that faster groups showed better coordination of movement changes and information flow being higher in faster groups, as shown by previous work [13], can thereby be directly explained by the higher (local) order that arises with higher individual speeds.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Finally, we demonstrate that the local side-by-side structure scales up to the global level, making the entire flock elongated in the direction perpendicular to the movement. This is similar to the way in which fish schools are elongated in the movement direction as a result of the frontto-back local configuration of neighbours [42,[62][63][64]. We note, however, that the elongated group shape was observed here for birds traveling together in a particular direction (in this case, towards evening roosts).…”
Section: Discussionsupporting
confidence: 83%